Crystal structure of thermally stable homodimeric cytochrome c′‐β from Thermus thermophilus. Issue 6 (1st June 2022) - Yoshimi, Taisuke; Fujii, Sotaro; Oki, Hiroya; Igawa, Takeshi; Adams, Hannah R.; Ueda, Kengo; Kawahara, Kazuki; Ohkubo, Tadayasu; Hough, Michael A.; Sambongi, Yoshihiro
Abstract : Structural and thermal stability analyses of Thermus thermophilus cytochrome c ‐β (TTCP‐β) are presented. It is shown that TTCP‐β exhibits higher stability than moderately thermophilic homologue from Methylococcus capsulatus, although both proteins have quite similar folding, heme environment, and subunit composition. Abstract : Cytochrome c ′‐β is a heme protein that belongs to the cytochrome P460 family and consists of homodimeric subunits with a predominantly antiparallel β‐sheet fold. Here, the crystal structure of cytochrome c ′‐β from the thermophilic Thermus thermophilus (TTCP‐β) is reported at 1.74 Å resolution. TTCP‐β has a typical antiparallel β‐sheet fold similar to that of cytochrome c ′‐β from the moderately thermophilic Methylococcus capsulatus (MCCP‐β). The phenylalanine cap structure around the distal side of the heme is also similar in TTCP‐β and MCCP‐β, indicating that both proteins similarly bind nitric oxide and carbon monoxide, as observed spectroscopically. Notably, TTCP‐β exhibits a denaturation temperature of 117°C, which is higher than that of MCCP‐β. Mutational analysis reveals that the increased homodimeric interface area of TTCP‐β contributes to its high thermal stability. Furthermore, 14 proline residues, which are mostly located in the TTCP‐β loop regions, possibly contribute to the rigid loop structure compared with MCCP‐β, which has only six proline residues. These findings, together with those from phylogenetic analysis, suggest that the structures of Thermus cytochromes c ′‐β, including TTCP‐β, are optimized for function under the high‐temperature conditions in which the source organisms live.